Configurations of e‐HRM – an empirical exploration. Issue 4 (2014) - ,; ,
Abstract : Purpose – The purpose of this paper is to investigate types, contexts and consequences of electronic HRM (e‐HRM) configurations to get a deeper understanding of the reasons, kinds and success of different e‐HRM types.Design/methodology/approach – The paper uses a cross‐sectional survey of senior HR persons and analyses data with exploratory methods, i.e. cluster analysis, classification tree analysis and analysis of variance.Findings – The results show that actually three configurations of e‐HRM – "non users", "operational users" and "power users" – exist. These can be explained by a sparse, yet meaningful set of contextual variables. All three configurations markedly contribute to organisational success, whereas the "power user"‐configuration exceeds the other configurations.Research limitations/implications – The employed e‐HRM typology shows a precursory status and the empirical study is exploratory in nature. Thus, searching for a clearer theoretical foundation, improving the hypothesising of variables and undertaking further empirical studies to replicate the findings are necessary future steps.Practical implications – Not always a maximum of electronic support seems to be indicated. Depending on the respective organisational context, even no electronic support, or else, a merely operational electronic support appears to be admissible; while, however, in larger and strategic‐oriented organisations full electronic support outperforms other configurations.Originality/value: –The paper focuses on different e‐HRM types and gives some first insights into reasons, kinds and success of different configurations. This should lead to a refined understanding of e‐HRM and evoke further research on the subject.